Sex plays a role in the construction of epiphytic bacterial communities on the algal bodies and receptacles of Sargassum thunbergii - Wang, Jing; Li, Yang; Yang, Zhibo; Sun, Tao; Yu, Xinlong; Zhao, Yayun; Tang, Xuexi; Xiao, Hui (Frontiers in Microbiology, 2022)
The community structures of epiphytic bacteria on the surface of macroalgae are closely related to their host algae, but there is a lack of research on the differences between the epiphytic bacterial communities of male and female algae and their reproductive tissues. In this study, high-throughput sequencing was used to compare epiphytic bacterial community structures on the intertidal macroalgae Sargassum thunbergii and their receptacles between male and female samples. The epiphytic bacteria on the male and female algal bodies and receptacles had similar community structures with a large number of shared bacteria, but the samples clearly clustered separately, and the abundances of dominant taxa, specific bacteria, and indicator species differed, indicating that epiphytic bacterial communities differed significantly between the male and female S. thunbergii and their receptacles. In addition, the abundance of many predicted functional genes was significantly different between epiphytic bacteria on male and female algal bodies and receptacles, especially metabolism-related genes, and the abundances of predicted functional genes of epiphytic bacteria were significantly higher on both types of male samples than on female samples. Our study confirmed that the sex of the host algae influenced the epiphytic bacterial community structures on algae and algal reproductive tissues, and this role was mainly related to the host metabolism. The results reveal the role of host plant sex in the formation of epiphytic bacterial communities. These findings are helpful for obtaining an in-depth understanding of the construction mechanism of algae-associated bacteria.